Comparative analysis of whole-genome sequencing of tumor and cfDNA in a neuroblastoma patient: a case report - Fransson, Susanne; Georgantzi, Kleopatra; Djos, Anna; Gaarder, Jennie; Svensson, Johanna; Anthonydhason, Vimala; Kogner, Per; Martinsson, Tommy; Umapathy, Ganesh (Frontiers in Oncology, 2025)
High-risk neuroblastoma (NB) poses significant challenges in pediatric oncology due to its resistance to conventional therapies, leading to relapse and poor prognosis. Copy number variations (CNVs) are strong prognostic factors in NB, prompting exploration into alternative methods for CNV profiling. We conducted whole-genome sequencing (WGS) of the circulating cell-free DNA (cfDNA) from a patient with NB and compared the WGS of the primary and relapsed tumor tissue. Our analysis revealed concordance between the somatic single nucleotide variants (SNVs), insertions and deletions (indels), and CNVs identified in the cfDNA and tumor WGS. Notably, WGS detected numerical chromosome imbalances, large and focal structural aberrations including amplifications in MYCN, CDK4, and MDM2, using low-input cfDNA. Furthermore, additional variants unique to the cfDNA, such as the rare MET (p.R970C) variant, were identified, possibly representing sub-clonal populations or variants present at metastatic sites. In conclusion, WGS analysis of cfDNA offers a noninvasive, cost-effective, rapid, and sensitive alternative for CNV profiling in patients with NB. This approach holds promise for improving prognostication and for guiding personalized treatment strategies in NB.